2016
DOI: 10.1186/s13613-016-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Practice of ultrasound-guided central venous catheter technique by the French intensivists: a survey from the BoReal study group

Abstract: BackgroundThe ultrasound (US)-guided technique has been recommended for central venous catheter (CVC) placement in critical care. However, several surveys have shown that the majority of physicians continue to perform landmark procedures. In our region, we have implemented special courses to promote the use of US with formal training and simulators. Ultrasound machines have also been installed in almost every ICU in our area. We designed a survey to investigate whether the training program established for year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…In a previous survey among emergency physicians in the United states, insufficient training and lack of equipment were identified as top barriers for the use of ultrasound during CVC placement [31]. Other authors identified 'no apparent need' and limited availability of ultrasound equipment as important reasons not to use ultrasound [10,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous survey among emergency physicians in the United states, insufficient training and lack of equipment were identified as top barriers for the use of ultrasound during CVC placement [31]. Other authors identified 'no apparent need' and limited availability of ultrasound equipment as important reasons not to use ultrasound [10,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasoundguided PIV insertion is also an effective alternative to CVC insertion in patients with difficult venous access. 17) We suggest using real-time ultrasound guidance to reduce the risk of vascular, infectious, and neurological complications during PIV insertion, particularly in patients with difficult venous access.…”
Section: )mentioning
confidence: 99%
“…Despite these recommendations, the use of ultrasound for central venous catheterization remains low [13]. We have been using the ultrasound guided method in our intensive care unit for two years now.…”
mentioning
confidence: 99%